2013
DOI: 10.1097/nna.0000000000000009
|View full text |Cite
|
Sign up to set email alerts
|

Work Engagement in Magnet®-Designated Hospitals

Abstract: This study provides empirical evidence about the relationships between WE and social/institutional characteristics of RNs. The findings are relevant to patients, nurses, nurse leaders, and organizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
6
0
2
Order By: Relevance
“…Further, the study claimed that the more the work experience, the greater the work engagement and the higher the chances of job retention. Another study 5 showed similar results and further noted that older nurses tend to have higher levels of work engagement as compared to younger ones. Doctors’ engagement is considered critical to avoid medical errors and diagnoses to provide quality health diagnostic and treatment services.…”
Section: Theoretical Frameworkmentioning
confidence: 53%
See 3 more Smart Citations
“…Further, the study claimed that the more the work experience, the greater the work engagement and the higher the chances of job retention. Another study 5 showed similar results and further noted that older nurses tend to have higher levels of work engagement as compared to younger ones. Doctors’ engagement is considered critical to avoid medical errors and diagnoses to provide quality health diagnostic and treatment services.…”
Section: Theoretical Frameworkmentioning
confidence: 53%
“…Most studies 5,33 on work engagement have looked at its link with demographic factors, while others 33 have investigated the relationship between engagement and burnout. The findings of this paper demonstrate the importance of work engagement 38 in the job performance of health professionals, doctors, nurses, and administrative staff.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study performed in Saudi Arabia (SA) among 980 nurses reported significant but weak positive correlations between nurses' age, education, and total work engagement scores [22]. Nevertheless, other previous literature has described inconsistent relationships between age and work engagement, requiring further investigations on this issue [23]. Some challenging factors include staff burnout and low turnover, which reduce the engagement of nurse employees in pediatric care units owing to secondary traumatic stress or compassion fatigue.…”
Section: Work Engagementmentioning
confidence: 99%